72 PROTEOME ANALYSIS OF SPHINGOSINE 1-PHOSPHATE-MEDIATED LIPID RAFTS IN HUMAN PULMONARY ENDOTHELIAL CELLS. (1st March 2007) - Zhao, J.; Singleton, P. A.; Dudek, S. M.; Natarajan, L.; Garcia, J. G.
Abstract : Rationale: Lipid rafts are detergent-insoluble plasma membrane microdomains implicated in membrane signaling and trafficking. We have demonstrated that the lysophospholipid sphingosine 1-phosphate (S1P) plays a critical regulatory role in the maintenance and enhancement of pulmonary vascular barrier function, which is dependent on lipid raft-mediated signaling events (Singleton et al. FASEB J 2005). In this study, we used two-dimensional electrophoresis analysis to determine the protein profiles in S1P-challenged lipid rafts of human pulmonary artery endothelial cells (HPAECs). Methods and Results: HPAECs were treated with S1P (1 μM) for 5 minutes and solubilized with 1% Triton X-100 at 4°C. The Triton X-100 insoluble and light density fractions were collected after discontinuous OptiprepTM gradient centrifugation. The isolated lipid rafts pellets were resolubilized in 50 μL of isoelectric focusing (IEF) buffer (7 M urea/2 M thiourea, 4% CHAPS). IEF was carried out on a linear electrophoresis gel strip (pH 3-10, 7 cm), with the second dimension performed on 4 to 20% SDS-PAGE gel. Analytic gels were stained using Imperial blue (Pierce). We observed several novel protein bands in lipid rafts isolated from S1P versus control-treated cells (1 μM, 5 minutes). To identify these novel proteins, analytic gels were stained with Sypro Ruby and images were analyzed using PDQuest (Bio-Rad). Novel protein spots were sliced from the gel, and gel pieces were swelled in 20 ng/μL modified trypsin and incubated at 37°C overnight after protein reduction and alkylation. The digested peptides were extracted with 5% formic acid and 50% acetonitrile. Protein identification was performed on ABI 4700 Maldi TOF/TOF MS. Two-dimensional gel image analysis results indicated that about 50 protein spots (such as discoidin domain receptor tyrosine kinase, myosin light chain kinase, pp60src, phosphodiesterase 6C, etc.) have over a threefold change after S1P (1 μM, 5 minutes) treatment compared with control. Further, antiphosphotyrosine immunoblots of two-dimensional gels indicated that S1P increased tyrosine phosphorylation of over 20 proteins, including the actin regulatory protein cortactin. Conclusions: Taken together, these results indicate that S1P induces recruitment of novel tyrosine kinases (ie, discoidin domain receptor tyrosine kinase, pp60src), with multiple tyrosine phosphorylation events in lipid rafts. These results suggest that recruitment of tyrosine kinases to lipid rafts may participate in S1P-induced signaling in HPAECs and could potentially play important roles in regulating S1P-induced pulmonary endothelial cells barrier function.